Anisotropic conductive adhesive and composition thereof

JP2025504764AActive Publication Date: 2025-02-19NOPION CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024539572
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-12-28
Filing Date
2022-12-28
Publication Date
2025-02-19
Estimated Expiration
2042-12-28

AI Technical Summary

Benefits of technology

【0023】 本発明の実施形態によれば、流動性が適切な範囲に制御された接着樹脂を含むことで、部品実装工程ステップで前記接着樹脂とはんだ粒子が基板の金属端子間に最大限に位置するようにする、自己組立型異方導電性接着剤を提供することができ、また優れた接着力と低い接触抵抗を有する自己組立型異方導電性接着剤を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025504764000001_ABST
    Figure 2025504764000001_ABST
Patent Text Reader

Abstract

The present invention provides an adhesive resin mixture having a controlled flowability, and a self-assembling anisotropic conductive adhesive including the adhesive resin mixture. The self-assembling anisotropic conductive adhesive including the adhesive resin mixture having a controlled flowability provides superior adhesion and contact resistance compared to conventional adhesives.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a self-assembling anisotropic conductive adhesive, and more particularly to a self-assembling anisotropic conductive adhesive having controlled flowability. [Background technology]

[0002] In the 21st century, with the advancement of information and communication devices, the trend towards higher integration, higher performance, lower cost, and smaller size of semiconductor packages is accelerating. Flexible displays, which have been attracting attention as the next generation of displays, have excellent flexibility and can be folded or rolled, so research into stable electrical / mechanical properties and higher integration of the attached micro components is progressing rapidly.

[0003] As a result, the development of high-density electronic packaging technology is progressing vigorously, and among the bonding technologies for such electronic packaging technology, a bonding method using anisotropic conductive adhesives (ACAs) has significant advantages such as low temperature processing and simplified process.

[0004] The anisotropic conductive adhesive is a material made by mixing metal powder or conductive polymer powder with a polymer binder. It combines the electrical, magnetic and optical properties of metal with the mechanical properties and processability of polymer, making it an essential core material for connecting display panel glass, driving ICs to flexible PCBs, etc.

[0005] Such an anisotropic conductive adhesive generally includes solder particles, a reducing agent, and an adhesive resin. As can be seen from Figures 1 to 3, during the component mounting process, the solder particles 31 in the anisotropic conductive adhesive 30 are positioned between the metal terminals of the board, so that the solder particles function as an electrical path, and the adhesive resin 32 in the anisotropic conductive adhesive functions as an adhesive.

[0006] However, since the adhesive resin has fluidity during the component mounting process, the adhesive resin and the solder particles may be positioned between the metal terminals of the board, but if the viscosity of the adhesive resin is too low, the solder particles and the adhesive resin may all flow out of the gap between the metal terminals of the board and be lost, resulting in a weakened adhesive force. Conversely, if the viscosity of the adhesive resin is too high, the fluidity of the adhesive resin and the solder particles may decrease, resulting in a problem that the adhesive resin and the solder particles may not be positioned between the metal terminals of the board during the component mounting process.

[0007] Therefore, there is a need for a self-assembling anisotropic conductive adhesive that has appropriate viscosity, allows the adhesive resin and solder particles to be properly positioned between the metal terminals of the substrate, and has appropriate fluidity to prevent the solder particles and adhesive resin from flowing out during the component mounting process. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Republic of Korea Patent Publication No. 10-2062482 Summary of the Invention [Problem to be solved by the invention]

[0009] The technical problem that the present invention aims to achieve is to provide a self-assembling anisotropic conductive adhesive containing an adhesive resin whose fluidity is controlled within an appropriate range.

[0010] Another technical problem that the present invention aims to achieve is to provide a self-assembling anisotropic conductive adhesive having excellent adhesive strength and low contact resistance.

[0011] The technical problems that the present invention aims to achieve are not limited to the above-mentioned technical problems, and other technical problems not mentioned will be clearly understood by a person having ordinary skill in the art to which the present invention pertains from the following description. [Means for solving the problem]

[0012] In order to achieve the above technical objectives, one embodiment of the present invention provides an adhesive resin mixture for SACA, which comprises a first epoxy resin having a plurality of epoxy groups in its molecule and a second epoxy resin having a viscosity of 100 cps or more and 500 cps or less.

[0013] In one embodiment of the present invention, the weight ratio of the first epoxy resin to the second epoxy resin may be 1:1.2 or more and 1:1.5 or less for the adhesive resin mixture for SACA.

[0014] In addition, in an embodiment of the present invention, the adhesive resin mixture may be an adhesive resin mixture for SACA, characterized in that it has a viscosity of 500 cps or more and 100,000 cps or less in a temperature range of 70°C or more and 250°C or less.

[0015] In an embodiment of the present invention, the first epoxy resin may be any one selected from the group including bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, bisphenol AF type epoxy resin, biphenyl type epoxy resin, naphthalene type epoxy resin, fluorene type epoxy resin, novolac type epoxy resin, phenol novolac type epoxy resin, orthocresol novolac type epoxy resin, glycidyl ether type epoxy resin, glycidyl amine type epoxy resin, alicyclic epoxy resin, aliphatic polyglycidyl type epoxy resin, dimer acid modified epoxy resin, rubber modified epoxy resin, urethane modified epoxy resin, acrylic modified epoxy resin, and silicone modified epoxy resin.

[0016] In addition, in an embodiment of the present invention, the first epoxy resin may be an adhesive resin mixture for SACA, characterized in that the weight average molecular weight (Mw) is 30,000 or more and 60,000 or less.

[0017] In an embodiment of the present invention, the second epoxy resin may be any one selected from the group including bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, bisphenol AF type epoxy resin, biphenyl type epoxy resin, naphthalene type epoxy resin, fluorene type epoxy resin, novolac type epoxy resin, phenol novolac type epoxy resin, orthocresol novolac type epoxy resin, glycidyl ether type epoxy resin, glycidyl amine type epoxy resin, alicyclic epoxy resin, aliphatic polyglycidyl type epoxy resin, dimer acid modified epoxy resin, rubber modified epoxy resin, urethane modified epoxy resin, acrylic modified epoxy resin, and silicone modified epoxy resin.

[0018] In addition, in an embodiment of the present invention, the second epoxy resin may be an adhesive resin mixture for SACA, characterized in that the epoxy equivalent is 10 g / ep or more and 200 g / ep or less.

[0019] In order to achieve the above technical objectives, another embodiment of the present invention provides a self-assembling anisotropic conductive adhesive with controlled fluidity, comprising conductive solder particles and the adhesive resin mixture of paragraph 1, and characterized in that the adhesive resin mixture of paragraph 1 has a viscosity of 500 cps to 100,000 cps in a temperature range of 70°C to 250°C, thereby allowing the solder particles and the adhesive resin mixture to be maximally positioned between metal terminals of a substrate during a component mounting process.

[0020] In one embodiment of the present invention, the solder particles may be a self-assembling anisotropic conductive adhesive having controlled fluidity, characterized in that the solder particles have a melting point between the reaction initiation temperature and the curing temperature of the conductive adhesive resin mixture.

[0021] In addition, in an embodiment of the present invention, the solder particles may be a self-assembling anisotropic conductive adhesive with controlled fluidity, characterized in that the solder particles include one or more selected from the group consisting of tin (Sn), copper (Cu), indium (In), silver (Ag), and bismuth (Bi). In addition, in an embodiment of the present invention, the solder particles may be a self-assembling anisotropic conductive adhesive with controlled fluidity, characterized in that the melting point is 70°C or more and 250°C or less.

[0022] In the embodiment of the present invention, the anisotropic conductive adhesive may be a self-assembling anisotropic conductive adhesive having controlled fluidity, characterized in that the anisotropic conductive adhesive is in a film or paste form. Effect of the Invention

[0023] According to an embodiment of the present invention, a self-assembling anisotropic conductive adhesive can be provided that includes an adhesive resin whose fluidity is controlled within an appropriate range, thereby maximizing the positioning of the adhesive resin and solder particles between the metal terminals of the substrate during the component mounting process step, and a self-assembling anisotropic conductive adhesive having excellent adhesive strength and low contact resistance can be provided.

[0024] The effects of the present invention are not limited to the above effects, but include all effects that can be inferred from the configuration of the invention described in the detailed description of the present invention or the claims. [Brief description of the drawings]

[0025] [Figure 1] FIG. 2 is a diagram showing the state of the conductive adhesive positioned between the substrates before the self-assembling anisotropic conductive adhesive is cured. [Diagram 2] 1A to 1C are diagrams showing the process in which the adhesive resin and solder particles are hardened in the step of mounting the self-assembling anisotropic conductive adhesive. [Diagram 3] FIG. 13 shows the connections located between the substrates after the self-assembled anisotropic conductor has cured. [Figure 4]FIG. 2 illustrates the state of a conductive adhesive disposed between substrates before a self-assembled anisotropic conductor provided by an embodiment of the present invention is cured. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] The present invention will now be described with reference to the accompanying drawings. However, the present invention may be embodied in various different forms and is not limited to the embodiments described herein. In addition, in order to clearly describe the present invention in the drawings, parts that are not relevant to the description are omitted, and similar parts are designated by similar reference numerals throughout the specification.

[0027] Throughout the specification, when a part is said to be "connected (connected, contacted, or coupled)" to another part, this includes not only the case where the part is "directly connected" to another part, but also the case where the part is "indirectly connected" via another member therebetween. Furthermore, when a part is said to "include" a certain component, this does not mean that the part excludes other components, but that the part may further include other components, unless otherwise specified.

[0028] The terms used in this specification are merely used to describe certain embodiments and are not intended to limit the present invention. A singular expression includes a plural expression unless the context clearly dictates otherwise. In this specification, the terms "include" or "have" specify the presence of a feature, number, step, operation, component, part, or combination thereof described in the specification, and do not preclude the presence or addition of one or more other features, numbers, steps, operations, components, parts, or combinations thereof.

[0029] Hereinafter, a self-assembling anisotropic conductive adhesive 30 with controlled fluidity according to an embodiment of the present invention will be described in detail with reference to the accompanying drawings.

[0030] According to one embodiment of the present invention, a conductive solder particle 31 and Adhesive resin mixture described laterand a viscosity of 500 cps to 100,000 cps inclusive in a temperature range of 70° C. to 250° C. containing the adhesive resin mixture, thereby providing an effect of maximally positioning the solder particles and the adhesive resin mixture 32 between the metal terminals 11 of the board during a component mounting process.

[0031] In the component mounting process step, the adhesive resin 32 in the adhesive resin mixture contained in the SACA 30 has fluidity and is therefore positioned between the metal terminals of the substrate, and as the adhesive resin in the SACA 30 hardens, it bonds the metal terminals of the substrate.

[0032] At this time, the fluidity of the adhesive resin 32 having the fluidity must be within an appropriate numerical range, and if the fluidity is too low, the fluidity of the adhesive resin 32 and the solder particles 31 is hindered, and they may not even be located between the metal terminals 21 of the substrate. Conversely, if the fluidity is too high, the adhesive resin 32 and the solder particles 31 may come off from between the metal terminals 21 of the substrates 10 and 20 due to the excessive fluidity in the step of applying heat and pressure to bond them, and ultimately the substrates 10 and 20 will not be bonded to each other, resulting in a decrease in the stability and reliability of the product.

[0033] Therefore, as described above, one embodiment of the present invention provides a SACA 30 that enhances the adhesive strength of the substrate by controlling the fluidity of the adhesive resin 32.

[0034] The adhesive resin 32 of the SACA 30 with adjusted fluidity will now be described.

[0035] In the present invention, the adhesive resin 32 of the SACA 30 with adjusted fluidity is mainly composed of an adhesive resin mixture for SACA of the embodiment described below, but the adhesive resin is not limited to the adhesive resin mixture for SACA of the embodiment described below, and any mixture that is the same as or equivalent to the adhesive resin mixture provided in one embodiment of the present invention and any adhesive resin that provides the same or equivalent effect should be interpreted as falling within the scope of the present invention.

[0036] The solder particles of the SACA30 with adjusted fluidity will be described below.

[0037] The role of the solder particles will now be described.

[0038] The solder particles used in the present invention may be conductive particles. By using such conductive particles, the solder particles are ultimately positioned between the substrates and serve as electrical paths between the electrodes of the substrates.

[0039] The melting point of the solder particles will be described below.

[0040] When electronic components are heated during the mounting process, the solder particles must melt to form a connection before the thermosetting resin hardens, and the viscosity of the thermosetting resin must be reduced to facilitate the aggregation of the molten solder particles in the heated state. Therefore, it is preferable that the melting point of the solder particles be between the reaction start temperature and the hardening end temperature of the thermosetting resin.

[0041] Therefore, the solder particles may be low-melting-point solder particles having a melting point of 70° C. or more and 250° C. or less. By using such low-melting-point solder particles, damage to various members of electronic components due to thermal history can be suppressed or prevented.

[0042] The composition of the solder particles will be described below.

[0043] The solder particles may include two or more of the group consisting of tin (Sn), indium (In), copper (Cu), silver (Ag), and bismuth (Bi). For example, the solder particles may be, but are not limited to, 60Sn / 40Bi, 52In / 48Sn, 97In / 3Ag, 57Bi / 42Sn / 1Ag, 58Bi / 42Sn, and 96.5Sn / 3.5Ag. However, the present invention is not limited to the above metal particles, and any configuration that can be easily modified and adopted by a person skilled in the art to achieve the effects of the present invention, such as a conjugated polymer conductive polymer, should be construed as belonging to the present invention.

[0044] In addition, when the solder particles are metal elements, they easily form an oxide film on the surface when they come into contact with oxygen in the air. When an electronic component such as a semiconductor chip is mounted using an anisotropic conductive adhesive containing solder particles, the formed oxide film causes a problem that electrical characteristics such as low conductivity and unstable bonding strength due to unstable contact resistance are generated. In order to solve this problem, in the step of mixing and dispersing the solder particles and the binder resin, solder particles whose wetting has been improved by a reducing agent such as a carboxylic acid can be used to strengthen the bond with the wiring or signal line contacts.

[0045] That is, when the solder particles are metal elements, there is a possibility that an oxide film is formed, so it is preferable that the oxide film of the solder particles is removed or controlled by a reducing agent.

[0046] The particle size of the solder particles will be described below.

[0047] The size of the solder particles can be selected according to the size (egpitch) of the conductive pattern to be applied, and as the size of the conductive pattern increases, solder particles with a larger particle size can be used.

[0048] The mixture ratio of the solder particles will be described below.

[0049] Taking into consideration fluidity and wettability, the solder particles may be contained in a ratio of 5 to 60 volume % of the total amount of the fluidity-adjusted SACA 30. If the ratio is less than 5 volume %, there is a risk that the terminals will not be connected due to a shortage of solder particles, and if the ratio is more than 60 volume %, there is a risk that an excessive amount of solder particles will remain, causing a bridge due to the connection between adjacent terminals, resulting in a short circuit.

[0050] Hereinafter, the physical properties and characteristics of the SACA30 having controlled fluidity will be described.

[0051] FIG. 4 is a diagram showing the state of a conductive adhesive disposed between substrates before a self-assembled anisotropic conductor provided according to one embodiment of the present invention is cured.

[0052] The SACA30 with adjusted fluidity preferably has a viscosity of 500 cps or more and 100,000 cps or less in the temperature range of 70° C. or more and 250° C. or less, as described above.

[0053] As described above, in the component mounting process step, the solder particles and the adhesive resin must be positioned between the metal terminals of the board as shown in FIG. 4. If the viscosity of the adhesive resin is less than 500 cps, the viscosity of the adhesive resin becomes too low and the fluidity increases, so that in the component mounting process step, the solder particles and the adhesive resin all flow out of the metal terminals of the board and are lost, and the adhesive strength of the final product is weakened. On the other hand, if the viscosity of the adhesive resin exceeds 100,000 cps, the viscosity of the adhesive resin becomes too high and the fluidity decreases, so that in the component mounting process step, the solder particles and the adhesive resin are not positioned between the metal terminals of the board and the adhesive strength of the final product is weakened. Therefore, it is preferable that the anisotropic conductive adhesive has a viscosity of 500 cps to 100,000 cps in the temperature range of 70°C to 250°C.

[0054] The fluidity-adjusted SACA30 can be used in a film or paste form. However, when mounting a substrate, it is preferable to use a film-type conductive adhesive, since the film-type is superior to the paste-type in terms of mounting cost of electronic components, thickness control, adhesive reliability, and other quality control.

[0055] In addition, as will be seen from the experiments described below, the fluidity-controlled SACA30 has an adhesive strength of 2.0 to 3.0 kgf / cm and excellent contact resistance, and is therefore more likely to be used as a mounting conductive adhesive in various industrial fields such as substrates, displays, and semiconductors than conventional anisotropic conductive adhesives.

[0056] Hereinafter, an adhesive resin mixture for SACA provided according to another embodiment of the present invention will be described.

[0057] In order to solve the above technical problems, another embodiment of the present invention provides an adhesive resin mixture for SACA, comprising: a first epoxy resin having a plurality of epoxy groups in its molecule; and a second epoxy resin having a viscosity of 100 cps or more and 500 cps or less at 20°C or more and 30°C or less.

[0058] In addition, since the adhesive resin mixture for the SACA needs to function to properly position the solder particles and adhesive resin between the metal terminals of the board during the component mounting process as described above, it is preferable that the adhesive resin mixture for the SACA has a viscosity of 500 cps or more and 100,000 cps or less in the temperature range of 70°C or more and 250°C or less, which is the melting temperature of the solder particles.

[0059] The constituent compounds of the adhesive resin will be described below.

[0060] The adhesive resin may include an adhesive resin mixture containing a plurality of epoxy resins, and the adhesive resin mixture may include a first epoxy resin containing a plurality of epoxy groups in its molecule and a second epoxy resin having an epoxy equivalent of 10 g / ep or more and 200 g / ep or less.

[0061] In this specification, "epoxy equivalent weight" means the molecular weight per epoxy group (g / eqiv) (meaning the average molecular weight divided by the number of epoxy groups per molecule); therefore, when the average molecular weight is fixed, a larger number of epoxy groups per molecule results in a smaller equivalent weight, and a smaller number of epoxy groups results in a larger equivalent weight.

[0062] In this case, the first epoxy resin contains a plurality of epoxy groups in the molecule, and the second epoxy resin has a viscosity of 100 cps to 500 cps at 20° C. to 30° C., preferably 100 cps to 500 cps at room temperature of 25° C., thereby making it possible to adjust the viscosity, self-assembling property, and physical properties of the composition.

[0063] In addition, the weight ratio of the first epoxy resin to the second epoxy resin may be 1:1 or more and 1:2 or less, and preferably 1:1.2 or more and 1:1.5 or less. When the first epoxy resin is added in excess by making the mixing ratio of the first epoxy resin to the second epoxy resin less than 1:1, the viscosity value becomes excessively high (when the viscosity exceeds the proposed range), and the self-assembly is not easy. When the second epoxy resin is added in excess by making the mixing ratio exceed 1:2, the above-mentioned physical properties are not ensured. Therefore, in order to avoid the above-mentioned problems, the mixing ratio of the first epoxy resin to the second epoxy resin may be 1:1 or more and 1:2 or less, and preferably 1:1.2 or more and 1:1.15 or less to obtain the best effect.

[0064] The first epoxy resin will now be described.

[0065] The first epoxy resin preferably has epoxy groups bonded to both side chains, thereby ensuring the properties of the epoxy groups, such as high adhesive strength, chemical resistance, moisture absorption resistance, and high insulation.

[0066] In addition, the first epoxy resin may be any one selected from the group including, for example, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, bisphenol AF type epoxy resin, biphenyl type epoxy resin, naphthalene type epoxy resin, fluorene type epoxy resin, novolac type epoxy resin, phenol novolac type epoxy resin, orthocresol novolac type epoxy resin, glycidyl ether type epoxy resin, glycidyl amine type epoxy resin, alicyclic epoxy resin, aliphatic polyglycidyl type epoxy resin, dimer acid modified epoxy resin, rubber modified epoxy resin, urethane modified epoxy resin, acrylic modified epoxy resin, and silicone modified epoxy resin, but is not limited to the above examples.

[0067] When the first epoxy resin is mixed, the mixing amount may be determined based on the weight ratio, and in this case, the weight ratio is a weight average molecular weight, and the weight average molecular weight (Mw) of the first epoxy resin to be mixed may be 30,000 or more and 60,000 or less.

[0068] If the weight average molecular weight of the first epoxy resin is less than 30,000, the final cured product may have excessive brittleness due to low toughness.

[0069] On the other hand, as the weight average molecular weight increases, the maximum crosslink density achievable by the reaction of the epoxy group decreases and the heat resistance tends to decrease. Therefore, when the weight average molecular weight of the first epoxy resin exceeds 60,000, the maximum crosslink density achievable by the reaction of the epoxy group decreases, resulting in a problem of a decrease in the final curing degree, and a problem of a decrease in heat resistance and unstable physical properties after curing.

[0070] In addition, it is preferable to use an epoxy resin having a softening point of 130° C. to 150° C. as the first epoxy resin. When a first epoxy resin having a softening point in the above temperature range is used, high heat resistance can be ensured.

[0071] If a composition is made only of epoxy with low viscosity and softening point in order to ensure fluidity during SACA bonding or for other purposes, it is very easy to adjust the fluidity, but there may be a problem that the physical properties become unstable after curing due to low heat resistance.

[0072] The second epoxy resin will now be described.

[0073] If the first epoxy resin is used alone, the viscosity value is excessively high at all temperatures between 70°C and 250°C and the melting temperature of the solder at which self-assembly occurs, and self-assembly of the adhesive resin mixture is not easy. Therefore, it is necessary to lower the viscosity of the adhesive resin mixture for SACA to make self-assembly easier, and the second epoxy resin is included for the above purpose.

[0074] In addition, the second epoxy resin must function as a diluent to reduce the viscosity of the adhesive resin mixture for the SACA, and must not impair the overall physical properties of the adhesive resin mixture for the SACA so as to ensure high reliability after the adhesive resin mixture for the SACA is cured. For this reason, it is preferable to use an epoxy resin having high heat resistance and glass transition temperature.

[0075] The second epoxy resin may be any one selected from the group including bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, bisphenol AF type epoxy resin, biphenyl type epoxy resin, naphthalene type epoxy resin, fluorene type epoxy resin, novolac type epoxy resin, phenol novolac type epoxy resin, orthocresol novolac type epoxy resin, glycidyl ether type epoxy resin, glycidyl amine type epoxy resin, alicyclic epoxy resin, aliphatic polyglycidyl type epoxy resin, dimer acid modified epoxy resin, rubber modified epoxy resin, urethane modified epoxy resin, acrylic modified epoxy resin, and silicone modified epoxy resin, but is not limited to the above examples.

[0076] In this case, the second epoxy resin may have an epoxy equivalent of 10 g / ep or more and 200 g / ep or less. If the epoxy equivalent is less than 10 g / ep, the number of reactive epoxy groups is too large, resulting in some remaining unreacted, thus causing a problem of impurities being generated. Conversely, if the epoxy equivalent is more than 200 g / ep, the number of reactive epoxy groups is too small, therefore, it is most preferable that the epoxy equivalent is 10 g / ep or more and 200 g / ep or less.

[0077] The present invention will be described in more detail below with reference to Production Examples, Comparative Examples and Experimental Examples, but the present invention is not limited to the following Production Examples and Experimental Examples.

[0078] Preparation Example 1 - Preparation of adhesive resin mixture for SACA In Preparation Example 1, various adhesive resin mixtures were prepared by mixing a phenol novolac epoxy resin as the first epoxy resin and a bisphenol F epoxy resin as the second epoxy resin. The specific preparation process is as follows.

[0079] Adhesive resin mixtures for 20 SACAs were prepared by mixing phenol novolac epoxy resin with 50,000 weight average molecular weight (Mw) and bisphenol F epoxy resin with 40,000 weight average molecular weight (Mw) in weight ratios of 1:0.1, 1:1.1, …, 1:1.9, and 1:2.0, and mixing was performed at 30°C for 30 min.

[0080] Table 1 below summarizes the above percentages.

[0081] [Table 1]

[0082] According to the above process, in Preparation Example 1, the adhesive resin mixture was successfully prepared.

[0083] Preparation Example 2 - Preparation of SACA with controlled fluidity In Production Example 2, a self-assembly type anisotropic conductive adhesive was produced, which contained the adhesive resin mixture produced in Production Example 1 and solder particles containing Bi and In metals. The specific production process is as follows:

[0084] The adhesive resin mixture (50 wt%) of entries 1 to 20 in Table 1 prepared in Preparation Example 1, solder particles (30 wt%), a reducing agent (5 wt%), a curing agent (10 wt%), and a silane coupling agent (5 wt%) were mixed to prepare a SACA.

[0085] At this time, the first epoxy resin and the second epoxy resin were mixed at 30° C. for 30 minutes to form a mixture, and other additives were further mixed into the mixture at 25° C. for 10 minutes.

[0086] Then, the mixture was mixed with the pretreated solder particles and a reducing agent at 25° C. for 10 minutes, and finally, the mixture was mixed with a hardener at 25° C. for 1 minute.

[0087] In this case, the mixing steps were all carried out using a paste mixer.

[0088] As a result, a self-assembling anisotropic conductive adhesive was successfully produced.

[0089] Preparation Example 3 - Preparation of SACA with controlled flow properties having different solder particle compositions In Preparation Example 3, various SACAs were manufactured by the same method as in Preparation Example 2, except that the Bi and In metals constituting the solder particles were changed to Sn, Ag, and Cu metals at a volume of 30 wt %.

[0090] By changing the metal element, we were able to manufacture SACA containing various solder particles, which shows that users can manufacture anisotropic conductive adhesives containing any metal element they desire.

[0091] Experimental Example 1 - Confirmation of viscosity of adhesive resin mixture In this Experimental Example 1, the viscosity of the adhesive resin mixture produced in Production Example 1 above was measured.

[0092] The specific experimental method is as follows. The experiment was carried out by using a rheometer to measure the minimum viscosity value in the temperature range of 70°C to 250°C.

[0093] [Table 2]

[0094] As can be seen from Table 2 above, the closer the mixing ratio of bisphenol F epoxy and phenol novolac epoxy is to 1:1, the higher the viscosity, and the closer it is to 1:2, the lower the viscosity.

[0095] In addition, as will be seen from the experimental examples described later, the adhesive resin mixture produced in the above Production Example 1 is the most suitable adhesive resin for a self-assembly type anisotropic conductive adhesive. Ratio between 1:1.2 and 1:1.5 is found to be the optimal ratio.

[0096] Experimental Example 2 - Adhesion Strength Verification Experiment In Experimental Example 2, adhesive strength was tested using various self-assembling anisotropic conductive adhesives prepared in Preparation Example 2 above.

[0097] The specific experimental method is as follows. 1.Equipment used: UTM (Universal Testing Machine) 2. Substrates used: PCB and FPCB adhesion (200 pitch) 3. Experimental conditions: tensile speed 50mm / min, 90°peel

[0098] Table 3 below summarizes the experimental results of Experimental Example 2.

[0099] [Table 3]

[0100] As can be seen from Table 3 above, the material having the best adhesive strength of 2.0 to 3.0 kgf / cm was SACA, which is a mixture of phenol novolac epoxy and bisphenol F epoxy in a ratio of 1:1.2 to 1:1.5.

[0101] From this experimental example, it was found that the best adhesive strength was obtained when phenol novolac epoxy and bisphenol F epoxy were mixed in a ratio of 1:1.2 to 1:1.5.

[0102] Experimental Example 3 In this Experimental Example 3, various self-assembling anisotropic conductive adhesives manufactured in the above Manufacturing Example 2 were used to test their surface resistance.

[0103] The specific experimental method is as follows. As can be seen from the above experimental results, the surface resistance is generally at a level of 1 or less, and is generally excellent.

[0104] Experimental Example 4 In this experimental example 4, an adhesive resin mixture was prepared by changing only the weight average molecular weight of the first epoxy resin in the above-mentioned preparation example 1, and a self-assembling anisotropic conductive adhesive containing these was prepared, and an experiment was conducted to confirm its adhesive strength.

[0105] The specific experimental method is as follows. 1.Equipment used: UTM (Universal Testing Machine) 2. Substrates used: PCB and FPCB adhesion (200 pitch) 3. Experimental conditions: tensile speed 50mm / min, 90°peel

[0106] [Table 4]

[0107] As can be seen from Table 4, the first epoxy resin provides the best adhesive strength when the weight average molecular weight is 30,000 or more and 60,000 or less.

[0108] This is because, when a first epoxy resin having the above weight average molecular weight is used, the effect of providing low brittleness and high crosslink density is provided.

[0109] Experimental Example 5 In Experimental Example 5, an adhesive resin mixture was prepared by changing only the epoxy equivalent of the second epoxy resin in Preparation Example 1, and a self-assembling anisotropic conductive adhesive containing the mixture was prepared and its physical properties were tested.

[0110] The specific experimental method is as follows. 1.Equipment used: UTM (Universal Testing Machine) 2. Substrates used: PCB and FPCB adhesion (200 pitch) 3. Experimental conditions: tensile speed 50mm / min, 90°peel

[0111] [Table 5]

[0112] As can be seen from Table 5, the second epoxy resin provides the most excellent effect when the epoxy equivalent is 100 g / ep or more and 200 g / ep or less.

[0113] This is because, when a second epoxy resin having the above epoxy equivalent is used, the number of reactive epoxy groups is optimized, so that most of the epoxy groups participate in the reaction and none remain as impurities.

[0114] The above description of the present invention is for illustrative purposes only, and a person having ordinary skill in the art to which the present invention pertains can easily modify the present invention into other specific forms without changing the technical idea or essential features of the present invention. Therefore, the above-described embodiments are illustrative in all respects and are not limiting. For example, each component described as a single type may be implemented in a distributed manner, and similarly, each component described as being distributed may be implemented in a combined form.

[0115] The scope of the present invention is defined by the claims set forth below, and all modifications and variations that fall within the meaning and scope of the claims and their equivalent concepts are included within the scope of the present invention. [Explanation of symbols]

[0116] 10: Second board 11: Connection terminal 20: First board 21: Electrode terminal 30: Self-assembly type anisotropic conductive adhesive 31: Solder particles 32: Adhesive resin included in adhesive resin mixture 33: Hardener 40: Connector 50: Cured resin layer

Claims

1. a first epoxy resin containing a plurality of epoxy groups in its molecule; a second epoxy resin having a viscosity of 100 cps or more and 500 cps or less at 20° C. or more and 30° C. or less; 1. An adhesive resin mixture for self-assembling anisotropic conductive adhesion, comprising:

2. The weight ratio of the first epoxy resin to the second epoxy resin is 1:1.2 to 1:1.

5.

2. The adhesive resin mixture for self-assembly type anisotropic conductive bonding according to claim 1.

3. The adhesive resin mixture has a viscosity of 500 cps or more and 100,000 cps or less in a temperature range of 70° C. or more and 250° C. or less.

2. The adhesive resin mixture for self-assembling anisotropic conductive bonding according to claim 1.

4. The first epoxy resin is any one selected from the group consisting of bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, bisphenol AF type epoxy resin, biphenyl type epoxy resin, naphthalene type epoxy resin, fluorene type epoxy resin, novolac type epoxy resin, phenol novolac type epoxy resin, orthocresol novolac type epoxy resin, glycidyl ether type epoxy resin, glycidyl amine type epoxy resin, alicyclic epoxy resin, aliphatic polyglycidyl type epoxy resin, dimer acid modified epoxy resin, rubber modified epoxy resin, urethane modified epoxy resin, acrylic modified epoxy resin, and silicone modified epoxy resin.

2. The adhesive resin mixture for self-assembling anisotropic conductive bonding according to claim 1.

5. The first epoxy resin has a weight average molecular weight (Mw) of 30,000 or more and 60,000 or less.

4. The adhesive resin mixture for self-assembling anisotropic conductive bonding according to claim 3.

6. The second epoxy resin is any one selected from the group consisting of bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, bisphenol AF type epoxy resin, biphenyl type epoxy resin, naphthalene type epoxy resin, fluorene type epoxy resin, novolac type epoxy resin, phenol novolac type epoxy resin, orthocresol novolac type epoxy resin, glycidyl ether type epoxy resin, glycidyl amine type epoxy resin, alicyclic epoxy resin, aliphatic polyglycidyl type epoxy resin, dimer acid modified epoxy resin, rubber modified epoxy resin, urethane modified epoxy resin, acrylic modified epoxy resin, and silicone modified epoxy resin.

2. The adhesive resin mixture for self-assembling anisotropic conductive bonding according to claim 1.

7. The second epoxy resin has an epoxy equivalent of 10 g / ep or more and 200 g / ep or less.

2. The adhesive resin mixture for self-assembling anisotropic conductive bonding according to claim 1.

8. Conductive solder particles; The adhesive resin mixture according to claim 1, The adhesive resin mixture according to claim 1 has a viscosity of 500 cps to 100,000 cps in the temperature range of 70° C. to 250° C., so that the solder particles and the adhesive resin mixture are positioned as far as possible between the metal terminals of the board during the component mounting process. A self-assembling anisotropic conductive adhesive having controlled fluidity.

9. The solder particles have a melting point between the reaction initiation temperature and the curing temperature of the conductive adhesive resin mixture. The self-assembling anisotropic conductive adhesive having controlled flowability according to claim 8 .

10. The solder particles include at least one selected from the group consisting of tin (Sn), copper (Cu), indium (In), silver (Ag), and bismuth (Bi). The self-assembling anisotropic conductive adhesive having controlled flowability according to claim 8 .

11. The solder particles have a melting point of 70° C. or more and 250° C. or less. The self-assembling anisotropic conductive adhesive having controlled flowability according to claim 8 .

12. The anisotropic conductive adhesive is in the form of a film or a paste. The self-assembling anisotropic conductive adhesive having controlled flowability according to claim 8 .

Citation Information

Patent Citations

  • Connection method, and assembly

    JP2016174126A

  • Manufacturing method of connection body, anisotropic conductive bonding material, and connection body

    JP2021068842A

  • Composition for use of an anisotropic conductive film, an anisotropic conductive film thereof and a semiconductor device using the same

    KR1020170011633A

  • Method for uniformly dispersing single layer nickel plated conductive particle in polymer film by applying megnetic field and method for producing anisotropic conductive file using the same

    KR102062482B1